A Review on Impact of Image Compression Techniques on Face Recognition Accuracy - Algubelly Yashwanth Reddy; P. Hasitha Reddy (AG Volumes, 2022)
Face recognition as well as identification in surveillance including security applications often need a very effective facial image compression technique. However, only heuristic refinement of codec is made as per face verification accuracy parameter when using either regular general image codecs or particular facial image compression techniques. Image as well as video-based face recognition systems are the becoming a hot research area because of the increasing use of face identification in daily life. Face recognition researchers are presently focusing their attention on the effects of factors such as posture, lighting, and expression. Despite the fact that most photos are saved and/or delivered in a compressed format, little research has been done just on impact of the compression on the face recognition. Face-recognition algorithms are compared in a still-to-still setting with the uncompressed training as well as gallery photos, as well as the various compression ratios for the probing images, in such paper’s review.